2018
DOI: 10.1111/tid.12968
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone safety in hematology patients: Pathways to optimizing Pneumocystis jirovecii pneumonia prophylaxis in hematology malignancy and transplant recipients

Abstract: Dapsone may be used for Pneumocystis jirovecii pneumonia (PJP) prophylaxis in hematology patients receiving immunosuppressive therapy or after hematopoietic stem cell transplant (HSCT) in the setting of trimethoprim-sulfamethoxazole (TMP-SMX) adverse drug reaction (ADR) history. Dapsone-induced hematological toxicities such as oxidative hemolysis may limit use in these patients and modern assessments of dapsone allergy cross-reactivity in non-HIV patients with a sulfonamide allergy are largely absent. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Our institution opted for 3‐day desensitization during the index transplant hospitalization, though it is likely that an expedited protocol (eg, 6 hours) would be similarly tolerated and effective. While our center's protocol includes pentamidine as second line for PJP prophylaxis in SOT recipients unable to tolerate TMP‐SMX, dapsone is an alternative option . Although the risk for cross‐reactivity between sulfonamide antibiotics and dapsone is low, there is a small but present risk of hemolytic anemia or methemoglobinemia …”
Section: Discussionmentioning
confidence: 99%
“…Our institution opted for 3‐day desensitization during the index transplant hospitalization, though it is likely that an expedited protocol (eg, 6 hours) would be similarly tolerated and effective. While our center's protocol includes pentamidine as second line for PJP prophylaxis in SOT recipients unable to tolerate TMP‐SMX, dapsone is an alternative option . Although the risk for cross‐reactivity between sulfonamide antibiotics and dapsone is low, there is a small but present risk of hemolytic anemia or methemoglobinemia …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dapsone-associated methemoglobinemia (8%) that we report is relatively similar to previous analyses. 6,8,9 Very few dapsone-treated patients in this cohort had evaluable lactate dehydrogenase, haptoglobin, or bilirubin assessments around the time of drug initiation of discontinuation. However, our assumption is that the mechanism for dapsone-associated anemia is likely hemolytic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of patients with hypersensitivity to TMP/SMX will also react to dapsone (up to 50%), so it should be avoided in those with lifethreatening reactions to TMP/SMX [14]. More recently, a study found no breakthrough PJP or cross-reactivity with TMP/SMX; however, it included only a small number of patients [56]. Other toxicities include methemoglobinemia, hemolytic anemia in those with glucose-6-phophate dehydrogenase deficiency, aplastic anemia, agranulocytosis, rash, nausea, and hepatitis.…”
Section: Epidemiology and Prevention (Tables 1 And 2)mentioning
confidence: 99%